New horizons for African rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Every year more and more Africans are choosing to eat rice. Consumption is rising by 5% a year and although this is a decelerating increase compared to the '70s, there is an ever-widening gap between demand and local supply. Until now this gap has...